Association of Eating Habits and Nutritional Status with Premenstrual Syndrome in Female Nursing Students in Tuban - Jihan Jaiza Zhafira Qatrunada; Taufiqurrahman; Nur Hatijah; Eny Sayuningsih (Politeknik Kesehatan Kemenkes Surabaya, 2025)
The high prevalence of premenstrual syndrome (PMS) among female nursing students may be associated with poor eating habits and inadequate nutritional status. This study aimed to analyze the relationship between eating habits, nutritional status, and the occurrence of PMS. A cross-sectional correlational study was conducted among 53 randomly selected female nursing students. Data were collected using a semi-quantitative Food Frequency Questionnaire (FFQ) for eating habits, BMI measurements for nutritional status, and a validated questionnaire for PMS symptoms. Data analysis included univariate and Chi-square tests. Most participants had poor eating habits (64.2%) and normal nutritional status (62.3%). The majority experienced moderate PMS symptoms (60.4%). Cross-tabulation showed that students with poor eating habits were more likely to report moderate to severe PMS. A significant association was found between eating habits and PMS (p = 0.000), indicating that poor dietary practices are linked to greater PMS severity. These findings suggest that improving eating habits may help reduce the risk and intensity of PMS symptoms in female students.